Kedaulatan dan Keadilan Allah dalam Kitab Obaja serta Relevansinya bagi Kehidupan Masa Kini - Winata, Jordi (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2023)
The purpose of this Research is to uncover the theological message contained in the Book of Obadiah, the shortest book in the Old Testament, which highlights the sovereignty and justice of God. This study explores key themes such as the judgment of Edom’s sins, the restoration of God's chosen people, and the concept of the "Day of the LORD," which reflects the fulfillment of His salvation plan. Utilizing a literature review method, this research analyzes how God's sovereignty is evident in the orchestration of history and how His justice is manifested in the punishment of sin and the restoration of world order. Additionally, the study examines the theological relevance of the Book of Obadiah for contemporary life, including the call to live in obedience, humility, love for others, and hope for ultimate restoration. The findings of this research affirm that God is a just and faithful Judge who brings justice and hope amidst the uncertainties of human life.